Risk Factors for and Outcomes Associated with Clinical Isolates of Escherichia coli and Klebsiella Species Resistant to Extended-Spectrum Cephalosporins among Patients Admitted to Canadian Hospitals - Marianna Ofner-Agostini; Andrew Simor; Michael Mulvey; Alison McGeer; Zahir Hirji; Melissa McCracken; Denise Gravel; David Boyd; Elizabeth Bryce (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Clinical features associated with Gram-negative bacterial isolates with extended-spectrum beta-lactamase (ESBL)- and AmpC-mediated resistance identified in Canadian hospitals is largely unknown. The objective of the present study was to determine the demographics, risk factors and outcomes of patients with ESBL- or AmpC-mediated resistant organisms in Canadian hospitals.